Retroperitoneal ectopic pregnancy: A case report - Trieu Quoc Tinh; Pham Thu Huyen; Le Thanh Dung; Nguyen Dinh Minh; Nguyen Thi Minh; Nguyen Van Son; Tran Quang Loc (Radiology Case Reports)
Retroperitoneal ectopic pregnancy is a rare form of ectopic pregnancy. In these cases, the gestational sac tends to attach near large retroperitoneal vessels, so when the sac ruptures, it can lead to severe bleeding, posing a life-threatening risk to the patient. Therefore, early diagnosis of ectopic pregnancy at this location is crucial. The diagnosis primarily relies on beta-hCG testing and imaging techniques, including ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI). Our case is an ectopic pregnancy in the retroperitoneum that was diagnosed early through ultrasound and CT and successfully treated with surgery.